CLINICAL AND FUNCTIONAL CHARACTERISTICS OF PATIENTS WITH EARLY AND LATE STAGES OF DEVELOPMENT OF PROFESSIONAL SENSORINEURAL HEARING LOSS - Инна Сергеевна Фунтикова; Елена Леонидовна Потеряева; Елена Леонидовна Смирнова (Медицина в Кузбассе)
To date, the mechanisms of early and late development of professional sensorineural hearing loss (PNST) remain poorly understood. Meanwhile, the analysis of associations of clinical and biochemical markers with the timing of the development of the disease allows us to justify and develop measures for effective treatment, rehabilitation and prevention.